An analytical evaluation of the Islamic websites - J. Badi, Maimona; Zeki, Akram M. (2011)
The multimedia computing revolution has been implemented in nearly all aspects of our life, including shopping, studying, research, and entertainment; thereby causing us to communicate differently because of it. Such change is inevitable, as revolutions displace traditional beliefs and practices. In the status quo, multimedia is not only advanced, but is advancing everything around us, as well as everything we use. This study aims to select five best Islamic websites and evaluate them in terms of implementing Multimedia tools, and how they use these tools to e-publish their information. The outcome of this research will help a great deal in setting up a guideline for the better global development of Islamic websites in terms of the use of multimedia tools. Consequently, this will lead to a better audience interaction, which will further aid in realizing the Islamic perspective in IT.